Analysis of Measurement Instruments in Guidance and Counseling: Validity and Reliability - Halimahtun Syaddiyah; Nurfarhanah; Zadrian Ardi (Mazidah: Journal Of Educational Research, 2025)
This study aims to review various national and international research on the analysis of validity and reliability of measurement instruments in guidance and counseling. Validity and reliability are two key indicators in determining the quality of psychological assessment tools. Validity reflects how well an instrument measures the intended construct, while reliability refers to the consistency of measurement results. Based on a review of several scientific journals, common approaches include exploratory and confirmatory factor analysis, internal consistency testing, and expert judgment validation. The review findings indicate that instruments developed through rigorous validity and reliability testing can enhance counseling effectiveness, provide more accurate diagnoses, and improve the quality of professional services. Therefore, it is essential for practitioners and researchers in guidance and counseling to continually evaluate and update the instruments they use.